Kinerja Keuangan Perbankan Konvensional di Indonesia Sebelum dan Selama Masa Pandemi Covid-19 - Iva Faizah; Dania Hellin Amrina (Fakultas Ekonomi Universitas Islam 45, 2021)
This study aims to analyze differences in the financial performance of conventional banks in Indonesia before and during the COVID-19 pandemic. The ratios used are Capital Adequacy Ratio (CAR), Return on Assets (ROA), Operating Expenses to Operating Income (BOPO), Loan to Deposit Ratio (LDR), and Net Interest Margin (NIM) using correlation test and paired sampled test. The results showed a significant decrease and difference between before and during the pandemic for the ratio of ROA, LDR, and NIM. for CAR and BOPO at banks in Indonesia, it turned out that there was an increase during covid. Still, based on different test results, there was no difference for the CAR ratio before and during the pandemic. Credit restructuring and a reduction in the reserve requirement ratio for banks are expected to stabilize banking conditions in Indonesia in the future